2004
DOI: 10.1111/j.1600-0838.2004.381.x
|View full text |Cite
|
Sign up to set email alerts
|

Fat metabolism in exercise – with special reference to training and growth hormone administration

Abstract: Despite abundance of fat, exclusive dependency on fat oxidation can only sustain a metabolic rate corresponding to 50-60% of VO(2max) in humans. This puzzling finding has been subject to intense research for many years. Lately, it has gained renewed interest as a consequence of increased obesity and physical inactivity imposed by Western lifestyle. Why are humans so poor at metabolizing fat? Can fat metabolism be manipulated by exercise, training, diet and hormones? And why is fat stored in specialized adipose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
11

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 290 publications
(389 reference statements)
0
24
0
11
Order By: Relevance
“…Boesch et al (2) revealed a decrease of IMCL in one subject performing a mountain bike ride over 3 h at about 70% of VO 2max , for the first time using 1 H-MRS to demonstrate that IMCL are metabolized during this form of exercise. In the following years, numerous reports on reduced IMCL levels during exercise were published and reviewed (17,20,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). It became obvious that both exercise duration and intensity are important factors in determining the reduction of IMCL (39).…”
Section: Various Other Influences Upon Imcl Levelsmentioning
confidence: 99%
“…Boesch et al (2) revealed a decrease of IMCL in one subject performing a mountain bike ride over 3 h at about 70% of VO 2max , for the first time using 1 H-MRS to demonstrate that IMCL are metabolized during this form of exercise. In the following years, numerous reports on reduced IMCL levels during exercise were published and reviewed (17,20,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). It became obvious that both exercise duration and intensity are important factors in determining the reduction of IMCL (39).…”
Section: Various Other Influences Upon Imcl Levelsmentioning
confidence: 99%
“…Além destes dois peptídeos, outras isoformas e fragmentos da molécula principal de GH estão presentes em quantidades variáveis na circulação em conseqüência de modificações após a etapa de tradução protéica (Baumann, 1991). Acredita-se que estas isoformas exerçam, também, importantes influências no desenvolvimento placentário, gravidez e lactação, porém ainda são pouco descritos na literatura (De Palo et al, 2001;Lange et al, 2004).…”
Section: Aspectos Gerais Do Ghunclassified
“…Os mecanismos responsáveis por estas alterações não estão totalmente esclarecidos na literatura. Apesar disso, outros diversos fatores podem influenciar a secreção do GH, incluindo o estado nutricional (Tirapegui et al, 2005), a quantidade de sono (Van Cauter, Copinschi, 2000) e de gordura corporal (Lange et al, 2004), o estresse (Bonifazi et al, 1998) e a prática da atividade física ou grau de treinamento (Gomes et al, 2004).…”
Section: Aspectos Gerais Do Ghunclassified
See 1 more Smart Citation
“…This can be explained by the heterogeneity of the groups, which was beyond our control, since the division of the groups in question occurred randomly. In addition, variables such as level of training [29], body composition [30], gender [31] and the age of individuals studied [32] may also modulate the release of this hormone [33,34].…”
Section: Citationmentioning
confidence: 99%